PENGEMBANGAN KURIKULUM PENDIDIKAN BERBASIS KEUNGGULAN LOKAL (PBKL) - Prihantini, - (2014)
Penelitian ini dilatarbelakangi oleh lemahnya pemahaman dan kepedulian peserta didik terhadap nilai-nilai keunggulan lokal. Hal tersebut merupakan akibat dari kurang tergarap dan terabaikannya potensi keunggulan lokal dalam proses pendidikan di sekolah. Tujuan penelitian adalah: (1) memperoleh gambaran tentang pengembangan kurikulum PBKL yang dilaksanakan oleh sekolah meliputi orientasi, perencanaan, implementasi, dan evaluasi kurikulum PBKL; (2) mengeksplorasi hubungan antara orientasi PBKL dengan perencanaan, implementasi, dan evaluasi kurikulum PBKL; (3) memperoleh gambaran perbedaan hasil belajar peserta didik berdasarkan implementasi pembelajaran PBKL. Lokasi penelitian adalah dua SMA penyelenggara PBKL di Kabupaten Sukabumi dan Kota Bogor. Metode penelitian menerapkan metode deskriptif evaluatif. Responden penelitian meliputi kepala sekolah, guru penanggung jawab program PBKL, guru pengampu mata pelajaran terintegrasi PBKL, dan siswa, yang ada di dua sekolah penyelenggara PBKL. Teknik sampling menggunakan purposive sampling. Teknik pengumpulan data menggunakan angket, wawancara, observasi, dan studi dokumentasi. Data yang dikumpulkan mencakup data kuantitatif dan data kualitatif (mixed data), dan data kualitatif berfungsi sebagai pendukung. Teknik analisis data kuantitatif menggunakan analisis Z-score dan T-score, uji korelasi menggunakan rumus korelasi Spearman Brown, dan uji beda menggunakan Mann Whitney U Test. Hasil penelitian ditemukan: (1) orientasi kepala sekolah dan guru di sekolah penyelenggara PBKL termasuk kategori sedang; (2) pengembangan kurikulum PBKL yang dilaksanakan oleh sekolah peyelenggara berbeda dalam perencanaan, implementasi, dan evaluasi kurikulum; (3) Orientasi PBKL yang berada pada kategori sedang di sekolah penyelenggara tidak berdampak pada perencanaan, implementasi, dan evaluasi kurikulum PBKL, karena rasa memiliki kurikulum lebih didasari oleh inisiatif dan komitmen bersama; (4) hubungan antara orientasi PBKL dengan pengembangan kurikulum (perencanaan, implementasi, evaluasi) di sekolah penyelenggara menunjukkan bahwa orientasi PBKL yang dimiliki kepala sekolah dan guru menentukan baik dan tidaknya pengembangan kurikulum PBKL; (5) terdapat perbedaan hasil belajar peserta didik di sekolah penyelenggara PBKL untuk mata pelajaran terintegrasi PBKL. Rekomendasi peneltian agar dilaksanakan penelitian tentang pengembangan kurikulum dengan menerapkan metode penelitian lain dan untuk meneliti hasil belajar peserta didik sebaiknya digunakan instrument dan sistem penilaian terstandar, serta gunakan mixed-data karena mixed-data dapat menghasilkan data dan informasi lebih obyektif dan komprehensif. Kata Kunci: pengembangan kurikulum, Pendidikan Berbasis Keunggulan Lokal (PBKL), orientasi, integrasi, hasil belajar kognitif dan psikomotor. The background to this research was the students' weak understanding and concern for local excellence values. The weakness was an impact of the ignored and less cultivated local excellence potentials in the educational processes in schools. The research aimed to: (1) Gain a description of the development of curriculum of local excellence-based education implemented in schools, covering orientation, planning, implementation, and evaluation of the curriculum of local excellence-based education; (2) Explore the correlation between the orientation of local excellence-based education and the planning, implementation, and evaluation of its curriculum; and (3) Find the differences in students' learning outcomes based on the implemented teaching and learning of local excellence-based education. The research took place in two senior secondary schools administering local excellence-based education in Sukabumi Regency and Bogor City. It employed evaluative-descriptive method. The respondents consisted of principals, teachers responsible for local excellence-based education programs, teachers teaching subjects integrated with local excellence-based education, and students in the two schools administering local excellence-based education. The technique of sampling used was purposive sampling. Data were collected using the techniques of questionnaire, interview, observation, and documentary study. The data gathered covered quantitative and qualitative data (mixed data), where the qualitative data functioned as supporting data. The techniques of quantitative data analysis were Z-score and T-score, correlation test using Spearman-Brown formula, and test for the difference using Mann Whitney U-Test. The research outcomes were: (1) The orientations of principals and teachers in the schools administering local excellence-based education were categorized as mediocre; (2) The development of curriculum of local excellence-based education by the administering schools was different in terms of planning, implementation, and evaluation of the curriculum; (3) The mediocre orientations of local excellence-based education in the two schools did not have an impact on the planning, implementation, and evaluation of the curriculum of local excellence-based education due to the sense of belonging that was based more on shared initiative and commitment; (4) The correlation between the orientations of local excellence-based education and the curriculum development (planning, implementation, evaluation) in the administering schools showed that the orientations owned by the principals and teachers determined whether the development of the curriculum of local excellence-based education would be good or not; (5) There were differences in the students' learning outcomes in the schools administering local excellence-based education for the subjects integrated with local excellence-based education. The research recommends that further research on curriculum development implementing other research methods be done and research on students' learning outcomes should use standardized systems of instrument and assessment and use mixed data, because mixed data can result in more objective and comprehensive data and information. Keywords: curriculum development, Local Excellence-Based Education (LEBE), orientation, integration, cognitive and psychomotor learning outcomes.